Development of fitlearn pjok android-based learning media application for junior high schools - Ariwibowo, Nur Fajar; Tuasikal, Abdul Rachman Syam; Kristiyandaru, Advendi (Bima Loka: Journal of Physical Education, 2025)
This study aims to develop and test the feasibility of the FitLearn PJOK Android-based application as a learning media for Physical Education, Sports, and Health (PJOK) in junior high schools. The research model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), which includes five stages of development. The research subjects involved junior high school students, PJOK teachers, as well as experts in learning materials and media. Data were obtained through questionnaires, interviews, and observations, then analyzed descriptively, quantitatively, and qualitatively. The results showed that in the analysis stage, the needs of students and teachers for interactive, easily accessible learning media that could clearly explain basic movement concepts were identified. The design stage produced an application design with multimedia content, a simple display, and interactive features in the form of videos, animations, and quizzes. Validation by subject matter and media experts showed that the application was valid with a feasibility score above 80%. The implementation stage with students and teachers showed a positive response with an average practicality score of 90.13%, which is categorized as very practical. Furthermore, summative evaluation showed that the use of the application was able to increase students' motivation, engagement, and understanding of PJOK material. Thus, the FitLearn PJOK application can be declared valid, practical, and effective for use as an innovative learning medium that supports the implementation of the Merdeka Curriculum at the junior high school level. However, further studies in various educational units are needed so that this application can truly be adopted nationally.